Canal irrigation and the hydrosocial cycle: The morphogenesis of contested water control in the Tungabhadra Left Bank Canal, South India - Mollinga, Peter P (Geoforum, 2014)
Using South Indian large-scale surface irrigation as a case, this paper combines emerging interdisciplinary conceptualisation in resource geography of the hydrological cycle as a hydrosocial cycle with Archer's theorisation of society's structure-agency dynamics as a morphogenetic cycle. Characteristic of large scale canal irrigation are a pronounced spatiality of social process, and a strongly cyclical nature of social interaction around water through seasonality and rotational supply, framed by irrigation infrastructure that is both grid and subject of water resources management practices. This allows an investigation of how human agency as the animator of structural elaboration reproduces and transforms a hybrid and multi-scale water control system, thus establishing a 'hydromorphogenetic' cycle of unequal irrigation water distribution. The detailed account of irrigation practice provides caution against simplified interpretations of dam + canals based irrigation as abodes of green revolution capitalist farming, and of the objectives of neoliberal irrigation reform policy. It is, lastly, suggested that the hydrosocial relations focus produces new insights and questions for irrigation studies, but that complexity and emergence rather than hybridity are the key analytical challenges.